The Study of the Verb Since the Early 20th Century and Complex Verbs in the Novel «The Path of Abai» (Eurasian Journal of Philology Science and Education, 2025)
This article explores how the grammatical categories and structure of verbs can be represented in metatagging. To achieve this, the study first examines complex verbs, their types, and formation characteristics, with a particular focus on scholars' perspectives on the topic. During the writing process, tables were constructed, and schematic representations of simple and complex verbs in the Kazakh language were developed. To further enhance the understanding of complex verb usage, the study aims to analyze their application and structural features in the novel «The Path of Abai». Specifically, the research involves selecting examples from the novel and classifying complex verbs based on the number of components. This approach is expected to contribute to expanding the body of knowledge on complex verbs. In this regard, the study sets the following objectives: to examine the general morphological characteristics of verbs as a major lexical category with extensive grammatical features, while also revisiting early 20th-century scholarly perspectives; to compare definitions of verbs across historical periods (from the early 20th century to the present); to analyze the lexical-grammatical classification of verbs and their grammatical categories over different periods; to identify the morphemes that generate grammatical categories and meanings; to highlight period-specific differences in the terminological system of category classification; to enumerate the structural groups of verbs; to determine whether variations in the number of components in complex verbs influence the semantics of complex actions; to illustrate how these distinctions are established; and to expand scientific knowledge on complex verbs by examining their use in “The Path of Abai”. One of the key issues addressed is the identification of the unique features of previous corpus-based studies on verb systems. Keywords: metatagging, “The Path of Abai” novel, mood forms, complex verb, verb structure.